Molecular detection and in vitro antioxidant activity of S-allyl-L-cysteine (SAC) extracted from Allium sativum - Sun, Y-E; Wang, W-D (Cellular and Molecular Biology, 2016)
It is well known that Allium sativum has potential applications to clinical treatment of various cancers due to its remarkable ability in eliminating free radicals and increasing metabolism. An allyl-substituted cysteine derivative - S-allyl-L-cysteine (SAC) was separated and identified from Allium sativum. The extracted SAC was reacted with 1-pyrenemethanol to obtain pyrene-labelled SAC (Py-SAC) to give SAC fluorescence properties. Molecular detection of Py-SAC was conducted by steady-state fluorescence spectroscopy and time-resolved fluorescence method to quantitatively measure concentrations of Py-SAC solutions. The ability of removing 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical using Py-SAC was determined through oxygen radical absorbance capacity (ORAC). Results showed the activity of Py-SAC and Vitamin C (VC) with ORAC as index, the concentrations of Py-SAC and VC were 58.43 mg/L and 5.72 mg/L respectively to scavenge DPPH, and 8.16 mg/L and 1.67 mg/L to scavenge •OH respectively. Compared with VC, the clearance rates of Py-SAC to scavenge DPPH were much higher, Py-SAC could inhibit hydroxyl radical. The ability of removing radical showed a dose-dependent relationship within the scope of the drug concentration.